Dataset of Global Change, altitudinal range shift and colonization of degraded habitats in mediterranean mountains (MIGRAME) - Antonio Jes?s P?rez Luque (Sierra Nevada Global Change Observatory. Andalusian Environmental Center, University of Granada, Regional Government of Andalusia, 2014)
In this datapaper we describe the dataset of the Global Change, Altitudinal Range Shift and Colonization of Degraded Habitats in Mediterranean Mountains (MIGRAME) project, which aims to asses the capacity of altitudinal migration and colonization of marginal habitats by Quecurs pyreanica Willd. forests in Sierra Nevada (southern Spain) considering two global change drivers: temperature increase and land use changes. The dataset includes information of the forest structure (diameter size, tree height and abundance) of the Quercus pyrenaica ecosystem in Sierra Nevada obtaided from 199 transect sampled at the treeline ecotone, mature forest and marginal habitats (abandoned cropland and pine plantations). A total of 3839 occurence records were collected and 5751 measurement recorded. The dataset is included in the Sierra Nevada Global-Change Observatory (OBSNEV), a long-term research project designed to compile socio-ecological information on the major ecosystem types in order to identify the impacts of global change in this area.
Keywords: Quercus pyrenaica forests; altitudinal migration; colonization of abandoned croplands; global change; Sierra Nevada (Spain); ocurrence data; measurement data; Occurrence